Toll-Like Receptor Evolution in Birds: Gene Duplication, Pseudogenization, and Diversifying Selection - Velová, Hana; Gutowska-Ding, Maria W; Burt, David W; Vinkler, Michal (Molecular biology and evolution, 2018)
Toll-like receptors (TLRs) are key sensor molecules in vertebrates triggering initial phases of immune responses to pathogens. The avian TLR family typically consists of ten receptors, each adapted to distinct ligands. To understand the complex evolutionary history of each avian TLR, we analyzed all members of the TLR family in the whole genome assemblies and target sequence data of 63 bird species covering all major avian clades. Our results indicate that gene duplication events most probably occurred in TLR1 before synapsids diversified from sauropsids. Unlike mammals, ssRNA-recognizing TLR7 has duplicated independently in several avian taxa, while flagellin-sensing TLR5 has pseudogenized multiple times in bird phylogeny. Our analysis revealed stronger positive, diversifying selection acting in TLR5 and the three-domain TLRs (TLR10 [TLR1A], TLR1 [TLR1B], TLR2A, TLR2B, TLR4) that face the extracellular space and bind complex ligands than in single-domain TLR15 and endosomal TLRs (TLR3, TLR7, TLR21). In total, 84 out of 306 positively selected sites were predicted to harbor substitutions dramatically changing the amino acid physicochemical properties. Furthermore, 105 positively selected sites were located in the known functionally relevant TLR regions. We found evidence for convergent evolution acting between birds and mammals at 54 of these sites. Our comparative study provides a comprehensive insight into the evolution of avian TLR genetic variability. Besides describing the history of avian TLR gene gain and gene loss, we also identified candidate positions in the receptors that have been likely shaped by direct molecular host-pathogen coevolutionary interactions and most probably play key functional roles in birds.
Keywords: molekulární evoluce; adaptive evolution; sekvence aminokyselin; duplikace genu; Toll-Like Receptors; positive selection; pseudogeny; Selection, Genetic; Birds; pattern recognition receptors; convergence; amino acid physicochemical properties; Gene Duplication; Animals; toll-like receptory; zvířata; Amino Acid Sequence; selekce (genetika); pseudogene; ptáci; Pseudogenes; Evolution, Molecular